An insight into Short-sprint coaches' knowledge and use of periodisation models and training methods - Sri Lankan context - Jeganenthiran Sellathurai; Nick Draper (IP Iermakov S.S., 2022)
Background and Study Aim. Periodised training strategies, due to their demonstrated success in improving athletic performance, have become increasingly utilised by coaches, athletes, and strength and conditioning practitioners as a key training methodology. As a consequence, a coach's knowledge of periodisation and training methods have become increasingly important for improvement of sport-sprint performance. Despite their importance of performance at the elite level, it was suspected that little is known about the Sri Lankan context. As a result, the purpose of this formative exploratory study was to examine knowledge about, and application of, periodisation and training methods by Sri Lankan elite-level coaches working with short-sprint athletes. Material and Methods. With institutional ethics approval, ten (n=10) expert short-sprint coaches volunteered to participate in the study, with data collected via semi-structured interviews. Data were analysed inductively, to identify 'patterns', 'themes' and 'categories' using the NVivo 12 qualitative software. Results. Four primary themes emerged from the interview data. These included "Periodisation models", "Monitoring training", "Strength development", and "Speed development". Findings revealed that coaches reported minimal or inadequate knowledge of periodised training and consequently, there did appear to be a gap between coach knowledge of periodised training, but additionally in regard to general training methodology; including aspect such as prescribing strength and speed training loads and, monitoring of training loads. The coaches believed that their knowledge was inadequate to support athletes with Olympic level potential. Conclusions. The findings identified a potential knowledge gap in coach education and development for elite sprint coaches in Sri Lanka.